2023
DOI: 10.1123/jpah.2022-0396
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Changes in Objectively Measured Moderate to Vigorous Physical Activity in Patients After Percutaneous Coronary Intervention: A Prospective Cohort Study

Abstract: Background: This study aimed to clarify factors affecting changes in moderate to vigorous physical activity (MVPA) in patients 1 to 3 months after undergoing percutaneous coronary intervention (PCI). Methods: In this prospective cohort study, we enrolled patients aged <75 years who underwent PCI. MVPA was objectively measured using an accelerometer at 1 and 3 months after hospital discharge. Factors associated with increased MVPA (≥150 min/wk at 3 mo) were analyzed in participants with MVPA < 150 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that those with a higher BMI performed less PA than those with a lower BMI. 28 , 29 In this study, we proposed using the model containing BMI owing to the potential contribution of this index to MVPA prediction, although the association with MVPA was not significant in the multivariate analysis. The predictive accuracy of PA scores was higher than that of standard questionnaires used in Japan.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported that those with a higher BMI performed less PA than those with a lower BMI. 28 , 29 In this study, we proposed using the model containing BMI owing to the potential contribution of this index to MVPA prediction, although the association with MVPA was not significant in the multivariate analysis. The predictive accuracy of PA scores was higher than that of standard questionnaires used in Japan.…”
Section: Discussionmentioning
confidence: 98%
“…For example, recent work in this cohort has shown that different combinations of brain pathologies may be associated with the person-specific rates of declining cognitive and motor function in the same individuals [11,12]. Studies have tried to assess change in daily physical activity [13,14]. In a previous study we used a modeling approach that provided average change for the entire cohort, but this study did not characterize person-specific rates of change, i.e., slope of longitudinal daily physical activity trajectories or its correlates [8].…”
Section: Introductionmentioning
confidence: 99%